Artificial intelligence in prosthodontics: a scoping review on current applications and future possibilities - Pareek, Mitali; Kaushik, Brahmansh (International Journal of Advances in Medicine, 2022)
Artificial intelligence (AI) is the data-driven disruptive technology of modern times. AI is reforming every field from space science to dentistry. Bio-medical provides various advantages over conventional diagnosis, treatment planning, patient documentation and management. Every field is implementing AI for the ease of both doctors and patients. In this present work, the review was done for the implementation of AI in prosthodontics. Prosthetic dentistry or prosthodontics is one of the branches of dentistry, mainly deals with replacement and rehabilitation of missing teeth with the help of fixed and removable prosthesis or with biocompatible substitutes like implants. In addition, it also helps to restore proper soft and hard tissues of the mouth, thereby improving the overall health status of the oral cavity. The following review highlighted the present-day technology of AI in dental prosthetics and its efficacy in diagnosing and constructing more patient-specific prosthesis. In conclusion, it is seen that AI is twin fold technology having both applications and limitations in dentistry.